Iodine-catalyzed electrophilic substitution of indoles: Synthesis of (un)symmetrical diindolylmethanes with a quaternary carbon center - Pillaiyar, Thanigaimalai; Sedaghati, Masoud; B. Mahardhika, Andhika; L. Wendt, Lukas; E. Müller, Christa (Beilstein Journal of Organic Chemistry, 2021)
A novel, versatile approach for the synthesis of unsymmetrical 3,3'-diindolylmethanes (DIMs) with a quaternary carbon center has been developed via iodine-catalyzed coupling of trifluoromethyl(indolyl)phenylmethanols with indoles. In contrast to previously reported methods, the new procedure is characterized by chemoselectivity, mild conditions, high yields, and scalability to obtain gram amounts for biological studies. Selected compounds were found to display affinity for cannabinoid receptors, which are promising drug targets for the treatment of inflammatory and neurodegenerative diseases.
Keywords: alkylation of indole; anti-inflammatory; binding affinity; cannabinoid receptors; diindolylmethane; unsymmetrical 3,3'-diindolylmethane

(untitled) - Garbe, T. R.; Kobayashi, M.; Shimizu, N.; Takesue, N.; Ozawa, M.; Yukawa, H. (J. Nat. Prod., 2000)

(untitled) - Queiroz, M. M. F.; Queiroz, E. F.; Zeraik, M. L.; Ebrahimi, S. N.; Marcourt, L.; Cuendet, M.; Castro-Gamboa, I.; Hamburger, M.; da Silva Bolzani, V.; Wolfender, J.-L. (J. Nat. Prod., 2014)

(untitled) - Pathak, T. P.; Osiak, J. G.; Vaden, R. M.; Welm, B. E.; Sigman, M. S. (Tetrahedron, 2012)

(untitled) - Gong, Y.; Sohn, H.; Xue, L.; Firestone, G. L.; Bjeldanes, L. F. (Cancer Res., 2006)

(untitled) - Sivaprasad, G.; Perumal, P. T.; Prabavathy, V. R.; Mathivanan, N. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Sashidhara, K. V.; Kumar, M.; Sonkar, R.; Singh, B. S.; Khanna, A. K.; Bhatia, G. (J. Med. Chem., 2012)

(untitled) - Sashidhara, K. V.; Modukuri, R. K.; Sonkar, R.; Rao, K. B.; Bhatia, G. (Eur. J. Med. Chem., 2013)

(untitled) - Kim, H. J.; Lee, H.; Lee, J. H.; Choi, D. H.; Jung, J. H.; Kim, J. S. (Chem. Commun., 2011)

(untitled) - He, X.; Hu, S.; Liu, K.; Guo, Y.; Xu, J.; Shao, S. (Org. Lett., 2006)

(untitled) - Imran, S.; Taha, M.; Ismail, N. (Curr. Med. Chem., 2015)

(untitled) - Jamsheena, V.; Shilpa, G.; Saranya, J.; Harry, N. A.; Lankalapalli, R. S.; Priya, S. (Chem.-Biol. Interact., 2016)

(untitled) - Ichite, N.; Chougule, M. B.; Jackson, T.; Fulzele, S. V.; Safe, S.; Singh, M. (Clin. Cancer Res., 2009)

(untitled) - Safe, S.; Papineni, S.; Chintharlapalli, S. (Cancer Lett., 2008)

(untitled) - Sujatha, K.; Perumal, P. T.; Muralidharan, D.; Rajendran, M. (Indian J. Chem., 2009)

(untitled) - Biersack, B. (Cancer Drug Resist., 2020)

(untitled) - Del Priore, G.; Gudipudi, D. K.; Montemarano, N.; Restivo, A. M.; Malanowska-Stega, J.; Arslan, A. A. (Gynecol. Oncol., 2010)

(untitled) - Kobayashi, M.; Aoki, S.; Gato, K.; Matsunami, K.; Kurosu, M.; Kitagawa, I. (Chem. Pharm. Bull., 1994)

(untitled) - Shiri, M.; Zolfigol, M. A.; Kruger, H. G.; Tanbakouchian, Z. (Chem. Rev., 2010)

(untitled) - Palmieri, A.; Petrini, M. (Synthesis, 2019)

(untitled) - Pillaiyar, T.; Uzair, M.; Ullah, S.; Schnakenburg, G.; Müller, C. E. (Adv. Synth. Catal., 2019)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Isanbor, C.; O’Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Prakash, G. K. S.; Wang, F. (Chim. Oggi, 2012)

(untitled) - Sarver, P. J.; Bacauanu, V.; Schultz, D. M.; DiRocco, D. A.; Lam, Y.-h.; Sherer, E. C.; MacMillan, D. W. C. (Nat. Chem., 2020)

(untitled) - He, Y.-Y.; Sun, X.-X.; Li, G.-H.; Mei, G.-J.; Shi, F. (J. Org. Chem., 2017)

(untitled) - Inamdar, S. M.; Gonnade, R. G.; Patil, N. T. (Org. Biomol. Chem., 2017)

(untitled) - Suárez, A.; Martínez, F.; Sanz, R. (Org. Biomol. Chem., 2016)

(untitled) - Zeng, X.-F.; Ji, S.-J.; Wang, S.-Y. (Tetrahedron, 2005)

(untitled) - Pillaiyar, T.; Gorska, E.; Schnakenburg, G.; Müller, C. E. (J. Org. Chem., 2018)

(untitled) - Deb, M. L.; Das, C.; Deka, B.; Saikia, P. J.; Baruah, P. K. (Synlett, 2016)

(untitled) - Jadhav, S. D.; Singh, A. (J. Org. Chem., 2016)

(untitled) - Lancianesi, S.; Palmieri, A.; Petrini, M. (Adv. Synth. Catal., 2012)

(untitled) - Sun, F.-L.; Zheng, X.-J.; Gu, Q.; He, Q.-L.; You, S.-L. (Eur. J. Org. Chem., 2010)

(untitled) - Pillaiyar, T.; Sedaghati, M.; Schnakenburg, G. (Beilstein J. Org. Chem., 2020)

(untitled) - Sasaki, S.; Ikekame, Y.; Tanayama, M.; Yamauchi, T.; Higashiyama, K. (Synlett, 2012)

(untitled) - Ling, Y.; An, D.; Zhou, Y.; Rao, W. (Org. Lett., 2019)

(untitled) - Pillaiyar, T.; Köse, M.; Sylvester, K.; Weighardt, H.; Thimm, D.; Borges, G.; Förster, I.; von Kügelgen, I.; Müller, C. E. (J. Med. Chem., 2017)

(untitled) - Xiao, J.; Wen, H.; Wang, L.; Xu, L.; Hao, Z.; Shao, C.-L.; Wang, C.-Y. (Green Chem., 2016)

(untitled) - Wen, H.; Wang, L.; Xu, L.; Hao, Z.; Shao, C.-L.; Wang, C.-Y.; Xiao, J. (Adv. Synth. Catal., 2015)

(untitled) - Felder, C. C.; Joyce, K. E.; Briley, E. M.; Mansouri, J.; Mackie, K.; Blond, O.; Lai, Y.; Ma, A. L.; Mitchell, R. L. (Mol. Pharmacol., 1995)

(untitled) - Yin, H.; Chu, A.; Li, W.; Wang, B.; Shelton, F.; Otero, F.; Nguyen, D. G.; Caldwell, J. S.; Chen, Y. A. (J. Biol. Chem., 2009)

(untitled) - Mei, G.-J.; Shi, F. (J. Org. Chem., 2017)

(untitled) - Wang, L.; Chen, Y.; Xiao, J. (Asian J. Org. Chem., 2014)

(untitled) - Li, X.; Tan, W.; Gong, Y.-X.; Shi, F. (J. Org. Chem., 2015)

(untitled) - Tan, W.; Du, B.-X.; Li, X.; Zhu, X.; Shi, F.; Tu, S.-J. (J. Org. Chem., 2014)

(untitled) - Liu, Y.; Zhang, H.-H.; Zhang, Y.-C.; Jiang, Y.; Shi, F.; Tu, S.-J. (Chem. Commun., 2014)

(untitled) - Lu, Y.-N.; Ma, C.; Lan, J.-P.; Zhu, C.; Mao, Y.-J.; Mei, G.-J.; Zhang, S.; Shi, F. (Org. Chem. Front., 2018)

(untitled) - Sun, X.-X.; Zhang, H.-H.; Li, G.-H.; He, Y.-Y.; Shi, F. (Chem. – Eur. J., 2016)

(untitled) - Zhou, L.-J.; Zhang, Y.-C.; Zhao, J.-J.; Shi, F.; Tu, S.-J. (J. Org. Chem., 2014)

(untitled) - Liu, H.; Zheng, C.; You, S.-L. (J. Org. Chem., 2014)

(untitled) - Čebular, K.; Stavber, S. (Pure Appl. Chem., 2018)

(untitled) - Breugst, M.; von der Heiden, D. (Chem. – Eur. J., 2018)